2022
DOI: 10.1002/ehf2.13957
|View full text |Cite
|
Sign up to set email alerts
|

Temporal trends in incidence, prevalence, and death of aortic stenosis in Korea: a nationwide population‐based study

Abstract: Aims We aim to determine the temporal trends of incidence, prevalence, and death of aortic stenosis (AS, I35.0) in an East Asian population. Methods and results Data for 3773 patients who were newly diagnosed with AS from 2006 through 2017 were extracted from the National Health Insurance Service in Korea. The age‐standardized incidence rate, prevalence rate, and death rate, survival rate (SR), and death risk of AS were calculated. Overall, the mean (standard deviation) age of AS patients was 69.9 (15.3) years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Many studies have attempted to identify the possible effects of sex on postoperative outcomes from severe AS, but the issue remains controversial. Numerous reports have shown that female sex is associated with a poor prognosis following SAVR for severe AS [ 3 , 11 , 12 , 21 , 22 , 23 ]. However, most of those studies focused on patients who had undergone combined SAVR and coronary artery bypass graft surgeries [ 3 , 21 , 22 ] and found poorer short-term mortality outcomes in females.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have attempted to identify the possible effects of sex on postoperative outcomes from severe AS, but the issue remains controversial. Numerous reports have shown that female sex is associated with a poor prognosis following SAVR for severe AS [ 3 , 11 , 12 , 21 , 22 , 23 ]. However, most of those studies focused on patients who had undergone combined SAVR and coronary artery bypass graft surgeries [ 3 , 21 , 22 ] and found poorer short-term mortality outcomes in females.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous reports have shown that female sex is associated with a poor prognosis following SAVR for severe AS [ 3 , 11 , 12 , 21 , 22 , 23 ]. However, most of those studies focused on patients who had undergone combined SAVR and coronary artery bypass graft surgeries [ 3 , 21 , 22 ] and found poorer short-term mortality outcomes in females. Previous studies have shown that females have a poorer long-term mortality outcome following coronary artery bypass graft surgery [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within this population, aortic valve stenosis (AS) is a representative geriatric disease, and the demand for surgical interventions in patients with significant AS is anticipated to escalate. 1,2 In patients with AS, increased afterload results in concentric hypertrophy, which leads to diastolic dysfunction and decreased coronary flow reserve. 3 In addition, patients with AS have many underlying diseases, such as coronary artery disease (CAD), hypertension, and diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…The age-standardized incidence, prevalence, and death rate of AS were approximately 1 person, 3 persons, and 0.2 persons per 100,000 in 2017, respectively. 1) …”
mentioning
confidence: 99%